THE EFFECT OF BOOKLET MEDIA HEALTH EDUCATION ON MOTHERS’ KNOWLEDGE ABOUT PICKY EATERS OF PRESCHOOL CHILDREN - Ajeng Salsabila Putri Kirana; Dadang Kusbiantoro; Harnina Samantha Aisyah (Journal of Vocational Nursing)
Introduction: Picky eating is a behavior that is difficult to eat in children with a strong tendency to be picky about food, consuming less varied food, limiting intake of certain foods, both familiar and new types of food to try. Good maternal knowledge is needed to be able to deal with picky eater behavior in children appropriately and prevent the picky eater problem from getting worse. Lack of knowledge causes limited information as a reference for action. Health education about picky eaters is carried out as an effort to increase mothers' knowledge about picky eaters. Carrying out health education using booklet media will help receive information about picky eaters more optimally. This research aims to analyze the effect of booklet media health education on mothers' knowledge about picky eaters in preschool children. Methods: This research design uses pre-experimental with one group pre-test and post-test. Using total sampling with a population of 40 respondents. The data collection method uses a questionnaire with 20 question items whose validity and reliability have been tested. The questionnaire is suitable to be used to measure mothers' knowledge about picky eaters in preschool children. Results: The results of the research using the Wilcoxon test obtained sig (0.000) <0.05) which means there is an influence on mothers' knowledge about picky eaters before and after health education. Conclusions: Booklet media health education has a significant effect on mothers' level of knowledge about picky eaters in preschool children.